Psychological wellbeing and treatment adherence among cardio-renal syndrome patients in Yemen: a cross section study - Adel Omar Laradhi; Adel Omar Laradhi; Yan Shan; Mohamed Elsayed Allawy; Mohamed Elsayed Allawy (Frontiers in Medicine)
BackgroundAnxiety and depression are associated with adverse outcomes in cardiorenal syndrome patients undergoing hemodialysis, including decreased quality of life, poorer clinical parameters, and lower treatment adherence.ObjectiveThis study aimed to examine the level of psychological wellbeing and its relationship with treatment adherence among dialysis patients with cardiorenal syndrome.MethodsThis cross-sectional descriptive study was conducted between February and May 2021 on convenience sampling of 100 patients in two dialysis centers in Hadhramout, Yemen. Patients’ depression and anxiety levels were assessed using the Hospital Anxiety and Depression Scale (HADS)—Arabic version, and patient treatment adherence was assessed using the Treatment Adherence Questionnaire (TAQ). Descriptive statistics, Pearson’s correlation analysis, and multiple linear regression analyzes were performed to analyze data with a significance level set at p < 0.05.ResultsThe mean age ± standard deviation of participants was 53.46 ± 14.24 years. Most (90%) of patients had moderate to high levels of anxiety and depression. Most of the patients (87%) had a low level of treatment adherence. The findings revealed that psychological wellbeing is significantly association with treatment adherence t = 2.577 (95% CI 0.029, 0.225), p = 0.011.ConclusionAnxiety and depression symptoms occurred more frequently among dialysis patients with cardiorenal syndrome, and there was a significant association between psychological wellbeing and treatment adherence. Our findings suggest that nurse managers should take into account that adding psychotherapies into the present cardiorenal syndrome treatment programs would improve patients’ clinical and psychological parameters and, consequently, their clinical outcomes while taking patient heterogeneity and resource limitations into consideration.